The effect of carbonized sago pith waste [SPW] on the characterization, physical and mechanical properties of vulcanized natural rubber / Nurul Adilah Shahrul Faizal - Shahrul Faizal, Nurul Adilah (2020)
Sago Pith Waste (SPW) is a fibrous residue that is rich in sago starch that is extracted from the rasped of the sago palm. It is an agricultural waste that is most commonly being disposed into the river. Thus, making the river polluted. This study aims to investigate the used and effect of different incineration temperature of SPW. The Sago Pith Waste Ash (SPWA) is used as a natural filler in the rubber compounding to test the mechanical and physical properties of the vulcanized rubber in the tensile strength, tensile modulus, elongation at break, hardness, abrasion-resistant and swelling index. Meanwhile, the sample particle of SPW and SPWA at 600 °C, 700 °C and 800 °C were characterized by particle size analysis (PSA), Fourier Transforms Infrared (FTIR) and also the rheology properties of the sample. The FTIR was conducted to confirm the presence of silica and carbonated group. The compounded rubber show an increasing pattern of hardness, tensile modulus and swelling index. Meanwhile, 5 phr loading was the optimum loading high abrasion resistant index and high elongation at break for a sample of SPWA 800 °C. Plus, SPWA 800 °C gives a high tensile strength at filler loading of 10 phr and 15 phr loading. As other compound samples show a lower value of tensile strength, only SPWA 600 °C that shows a positive increment of tensile strength as the filler loading increase. Generally, SMR L filled with SPWA can give a better improvement in the mechanical properties of the compounded rubber. Thus, can be considered to be used as a natural filler for future usage.